Evaluation of Lesson Plan and Learning Implementation in Physical, Sports and Health Education Using the Curriculum 2013 in Junior High Schools in Kediri, East Java - Imawati, Veni; Rumini, Rumini; Sulaiman, Sulaiman (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aimed analyzing and evaluating the appropriateness of lesson plan, analyzing and evaluating the conformity of lesson plan compiled with the implementation of learning, and analyzing the conformity of the Physical Health Education Learning (called PJOK) implementation with the conformity of Minister of Education and Culture of the Republic of Indonesia Regulation (called Permendikbud) Number 22 of 2016 about Curriculum 2013 of PJOK in Public Junior High Schools, Kediri. This research is evaluation research that analyzes lesson plans and implementation of learning by referring to the Minister of Education and Culture Regulation Number 22 of 2016 about Curriculum 2013. The sources and subjects of this study were teachers, assistant principal of academic affairs and curriculum, and tutor teachers. Data were collected through observation, interviews, and documentation. Mix method analysis technique with descriptive qualitative and quantitative was used based on four components include data collection, data reduction, data presentation or display, concluding. The results of this study were: percentage of lesson plan conformity compiled by PJOK teachers was 92.78%, the percentage of conformity for learning implementation was 86.37%. Based on the analysis results, it could be concluded lesson plan compiled was categorized very good, learning implementation carried out in Junior High Schools Kediri was categorized very good, and the level of conformity of learning implementation with lesson plans had been done well.